1997
DOI: 10.1139/f96-340
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of suspended particulate matter and zooplankton to MeHg contamination of the food chain in midnorthern Quebec (Canada) reservoirs

Abstract: Suspended particulate matter (SPM) retained by continuous-flow centrifugation, suspended matter of 20-150 mu m diameter, and zooplankton exceeding 150 mu m were sampled in the LG-2 and LA-1 reservoirs and in four natural lakes in northern Quebec during June, August, and September 1992 and 1993. Inorganic Hg concentrations in the three compartments did not differ significantly between the reservoirs and natural lakes, but methyl mercury (MeHg) concentrations in SPM (mean of 0.05 ppm) and zooplankton (up to 0.84… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 21 publications
3
13
0
Order By: Relevance
“…The main discrimination between MeHg and inorganic Hg in aquatic systems occurs during trophic transfer between biota at lower trophic levels, with the result that the proportion of MeHg in total Hg increases from 24% in phytoplankton to 96% in fish (Becker & Bigham 1995). Similar results have been reported by Watras & Bloom (1992), Plourde, Lucotte & Pichet (1997), Watras et al . (1998) and Bowles et al .…”
Section: Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…The main discrimination between MeHg and inorganic Hg in aquatic systems occurs during trophic transfer between biota at lower trophic levels, with the result that the proportion of MeHg in total Hg increases from 24% in phytoplankton to 96% in fish (Becker & Bigham 1995). Similar results have been reported by Watras & Bloom (1992), Plourde, Lucotte & Pichet (1997), Watras et al . (1998) and Bowles et al .…”
Section: Methodssupporting
confidence: 92%
“…1996; Tremblay et al . 1996; Plourde, Lucotte & Pichet 1997; Atwell, Hobson & Welch 1998) and provided detailed descriptions of temporal changes in accumulation rates (Thompson, Hamer & Furness 1991; Thompson, Furness & Walsh 1992). However, the mechanisms regulating MeHg formation, its initial incorporation in pelagic and benthic food chains, and subsequent trophic transfer, remain controversial (Watras et al .…”
Section: Introductionmentioning
confidence: 99%
“…Even for the other elements the size fractions were often different for a given lake and date, but the differences were less consistent across lakes and dates (i.e., the date x size interaction within lakes accounted for the largest proportion of the variation). Similarly, other studies that tested for differences in MeHg concentrations across zooplankton size fractions found significant differences (Back et al, 2003; Cleckner et al, 2003; Kainz et al, 2002; Masson and Tremblay, 2003; Paterson et al, 1998; Plourde et al, 1997; Tremblay et al, 1998). However, our review of the literature revealed that most studies (74%) do not separate zooplankton size fractions.…”
Section: Discussionmentioning
confidence: 73%
“…Our study did not include data for mercury accumulation by nonalgal particulate matter, which is known to be a significant Hg source to nonselective grazers such as Daphnia in some natural systems (29). In these experiments, the tanks were low in nonalgal particulates.…”
Section: Resultsmentioning
confidence: 99%